KRITIK TERHADAP PEMAHAMAN KRISTEN PROGRESIF TENTANG KESELAMATAN: PERSPEKTIF ALKITABIAH YANG TERPINGGIRKAN - Padan, Stefanus (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2024)
The saving work of Jesus Christ on the cross is a central pillar in Christianity, affirming that human salvation can only be obtained through faith in Him. So the purpose of writing this article is to criticise the progressive Christian understanding of salvation, this research uses a qualitative approach with content analysis, which is concerned with the progressive Christian understanding, the doctrine of salvation. When paying attention to the correct doctrine of salvation, it can be concluded that the progressive Christian understanding of salvation is inclusive, so researchers can say that this movement is not in accordance with biblical truth and even contradicts the truth of God's word. The conclusion of this article is that salvation in Christ is exclusive, this cannot be changed by humans, because exclusive salvation is a great gift for every believer..